Analisis Penegakan Hukum Pelanggaran Merek Dagang Kasus Louis Vuitton dan Louis Vuiton Dak - Ni Ketut Ayu Diah Sapitri (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Trademarks not only serve as product identities but also represent the reputation and trust built by a company over the long term. In increasingly fierce global competition, legal protection for brands, especially well-known brands, is crucial. This study examines the legal implications of alleged trademark infringement by the Louis Vuitton Dak restaurant in Korea, which resembles the luxury brand Louis Vuitton. The purpose of the study is to analyze the application of Law Number 20 of 2016 concerning Trademarks and Geographical Indications and to assess the effectiveness of law enforcement against such violations. The method used is normative juridical with a statutory and conceptual approach. The analysis focuses on similarities in principle, the element of bad faith in trademark registration, and violations of exclusive rights to well-known brands. The results of the study indicate that although regulations have provided protection, law enforcement in practice still faces various obstacles and has not fully created a deterrent effect.